Plastic surgery and celebrity behavior change: Hiding and revealing - Lucas Monteiro Chaves; Isabella Wuillaume Marino; Aguinaldo Gonçalves (Revista Brasileira de Cirurgia Plástica, 2024)
Introduction: The recent Resolution of the Federal Council of Medicine (CFM) No. 2,336/23, which allows for broader dissemination of medical services, sheds light on the relationship between Plastic Surgery and the media. This, in addition to body dissatisfaction and sociocultural issues, is a factor that contributes to women representing 86.3% of recipients of procedures in this specialty worldwide. The objective is to develop a reference panel of real situations of how female celebrities publicly address their plastic surgeries in the media. Method: A qualitative study of the Descriptive-Analytical Essay type was carried out with online data collection. Publications from three nations, Brazil, the United Kingdom, and the United States of America, from websites, magazines, newspapers, and social media materials were used. Results: The construction of an evolutionary reference panel consisting of real situations reveals the sequence of two main phases: concealment and unveiling. In the first, female celebrities denied that their changes in physical appearance were the result of surgical interventions, as in the emblematic cases of actresses Marilyn Monroe and Jennifer Laurence and television star Kim Kardashian. Regarding the revelation, especially in Brazil, famous personalities began to treat their plastic surgeries with greater transparency, such as singer Anitta and TV presenter Xuxa. On social networks, it became common to find users documenting their own experiences with procedures in this specialty. Conclusion: Plastic surgery probably gained a greater presence in the media with the popularization of cosmetic surgery, a process in which the acceptance of celebrities and the publicity of procedures are significant.